Long-term risk of type 2 diabetes in relation to habitual iron intake in women with a history of gestational diabetes: a prospective cohort study(1)(2) - Bao, Wei (Am J Clin Nutr, 2016)
Background: An iron overload may induce pancreatic islet damage and increase risk of diabetes. Women with a history of gestational diabetes mellitus (GDM) are at high risk of developing type 2 diabetes mellitus (T2DM) after pregnancy. Objective: We aimed to examine the association of habitual iron intake with long-term risk of T2DM in this high-risk population. Design: We included 3976 women with a history of GDM from the Nurses’ Health Study II cohort as part of the ongoing Diabetes & Women’s Health Study. The women were followed up through 2009. Iron intake was assessed with the use of a validated food-frequency questionnaire in 1991 and every 4 y thereafter. We used Cox proportional hazards models to estimate HRs and 95% CIs. Results: We documented 641 incident T2DM cases during 57,683 person-years of observation. Adjusted HRs for T2DM for the highest quartile compared with the lowest quartile were 1.64 (95% CI: 1.20, 2.25; P-trend = 0.02) for total iron intake and 1.80 (95% CI: 1.18, 2.74; P-trend = 0.005) for dietary heme iron intake. In addition, women who consumed ≥30.0 mg supplemental Fe/d, compared with nonusers, had an adjusted HR of 1.83 (95% CI: 1.25, 2.70; P-trend = 0.002). Conclusion: In women with a history of GDM, greater intakes of total iron, dietary heme iron, and supplemental iron were associated with higher risk of T2DM.